Immune checkpoint inhibitor therapy in advanced cervical cancer: Deepened response with prolonged treatment and repeat response to re-initiation of therapy - Jennifer Wolf; Yiquing Xu (Elsevier, 2023)
Immune checkpoint inhibitors (ICI) were approved in June 2018 for second line treatment of metastatic cervical cancer after progression on platinum-based chemotherapy. A cohort of 10 patients who received single agent ICI as second line treatment was examined, with an initial analysis published in July 2021. We performed an updated review of the duration of treatment response, outcome off treatment after 2 years of therapy, and outcome after re-initiation of ICI. Excluding 4 patients from the original report who subsequently experienced progression of disease and/or death, 6 patients were followed for 40 months (range, 39.2-50.8 months), and all achieved complete response (CR) as their best response after prolonged treatment, including 3 with initial partial response (PR). Four patients discontinued treatment, and two developed asymptomatic recurrence, were both re-initiated on ICI, and reached a CR and PR. The combined positive score (CPS) was variable among responders and non-responders, but levels were highest among the 2 patients off treatment who remained without evidence of disease. This update on prolonged follow up demonstrates that patients who respond to immune checkpoint inhibitors may deepen their response with prolonged treatment, have durable response off treatment and respond again to re-treatment in the event of recurrent disease. A higher CPS score may predict prolonged remission off treatment.